Synergistics Effect Of Cow Urine And Essential Oils Against Bacterial Isolates (Journal of Pharmaceutical Negative Results, 2023)
Cow urine shows a synergistic effect with various naturally occurring oils and herbs. In this study, we analyzed how the antibacterial activity of cow urine gets enhanced in the presence of essential oils. The observations suggested that 0.5% or 1% essential oil in combination with cow urine makes cow urine activity better than raw cow urine. Essential oils contain active components and phenolic-like compounds as active ingredients that enhance their antibacterial properties. These active components degrade the bacterial cell wall and inhibit bacterial survival in the oil’s environment.A total of 15 samples were prepared from cow urine (CU+0.5% E.O. and CU+1% E.O.). The mixture of cow urine and essential oils were processed and shows better activities than raw cow urine. The activity of all these samples is because of phenolic groups present in cow urine and essential oils.The activity is carried out by agar well diffusion technique against various bacterial isolates and the zone of inhibition was measured in mm. The essential oils of Ginger, Spearmint, Star anise, and Clove were found highly effective in the presence of Cow Urine against the Escherichia coli and Staphylococcus aureus followed by Klebsiella pneumoniae and Bacillus subtilis. It has been concluded from the present study that the (treated) cow urine enhances the activity of essential oils and showed a synergistic effect against the bacterial isolates.